INFORMATIONAL SINGULARITY OF SELF-CONSCIOUSNESS - JAUED, LUCAS (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The main objective of this article is to demonstrate that there is a form of self- consciousness where the amount of information generated by (q) (a set of predictions of sensory results, whether interoceptive or exteroceptive, of hypothetical actions) is a direct function of the degree of certainty that the individual attributes to (q). In this context, information is quantified in terms of a direct relationship with the degree of certainty that the individual has in relation to his/her own internal states